Case report: Meningitis and intracranial aneurysm caused by mixed infection of oral microflora dominated by anaerobes - Cheng, Hongjiang; Xu, Lina; Yang, Fengbing; Jia, Longbin; Zhao, Doudou; Li, Huimin; Liu, Wei; Li, Yujuan; Liu, Xiaoli; Geng, Xia; Guo, Jiaying; Ling, Chen; et al. (Frontiers in Neurology, 2022)
Introduction Meningitis caused by oral anaerobic bacteria is rare, especially when complicated with an infected intracranial aneurysm. This paper has described an extremely rare case of bacterial meningitis caused by a mixed infection of oral microflora dominated by anaerobes, which developed cerebral infarcts, brain abscess, intracranial aneurysm, and severe hydrocephalus during treatment. Case report We describe a 65-year-old male patient who was presented with fever and headache as the initial symptoms and then developed left ophthalmoplegia, right hemiplegia, and disturbance of consciousness. Brain imaging showed that intracranial lesions were increased progressively, and cerebral infarcts, brain abscesses, intracranial aneurysm, and severe hydrocephalus were appeared gradually. Eventually, we diagnosed it as anaerobic meningitis by making deoxyribonucleic acid sequencing from the brain abscess pus. After using an anti-microbial regimen that can sufficiently cover anaerobes, the patient's condition was effectively controlled. Conclusion Anaerobic meningitis can cause a series of intracranial complications. Among them, the intracranial aneurysm is extremely rare. When evidence shows that the infection originates from oral flora, physicians should consider the possibility of this type of encephalitis. An early diagnosis and timely treatment are crucial to improving the prognosis.